Mother India - Khan, Mehboob; Irani, Faredoon A.; Nargis; Dutt, Sunil; Kumar, Rajendra (Eros International, 2005)
Mehboob Khan's 1957 blockbuster is a conservative, virile epic of rural life. Radha, played by screen queen Nargis, is a strong, passionate earth mother, tilling the soil with the plough on her back when there are no oxen, raising her children alone and exploited by a local moneylender. Her son conceives a fanatical hatred for this man; his obsession, coupled with Radha's need to live within the boundaries of the law and common decency, ends in classical tragedy. [guardian.co.uk]